RECONSTRUCTING ISLAMIC EDUCATIONAL GOVERNANCE THROUGH PESANTREN VALUES: TOWARD GLOBALLY COMPETITIVE ISLAMIC BOARDING SCHOOLS - Abdul Halim; Ahmad Tanzeh; Kojin; Mujamil (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The transformation of global education demands that Islamic boarding schools (pesantren) develop adaptive educational governance without eliminating their identity and values. However, most previous studies have focused more on leadership, educational management, or partial modernization of Islamic boarding schools, thus failing to produce a model of Islamic education governance that integrates Islamic boarding school values ​​as the primary foundation of institutional development. This study aims to reconstruct Islamic education governance based on Islamic boarding school values ​​toward superior and globally competitive Islamic boarding schools. The study used a qualitative approach with a multi-site study design at the Salafiyah-Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo, and Al Qodiri Islamic Boarding School in Jember. Data were obtained through in-depth interviews, participant observation, documentation, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data presentation, and drawing and verifying conclusions. The results of the study show that effective Islamic education governance is built through the integration of value-based leadership, Islamic boarding school organizational culture, collaborative governance, integrative curriculum, human resource development, continuous quality assurance, and value-based digital innovation.sincerity, trust, deliberation, brotherhood, And service. This research resulted inIslamic Education Governance Model Based on Islamic Boarding School Valueswhich strengthens institutional quality, organizational sustainability, and the global competitiveness of Islamic boarding schools without abandoning the character and identity of Islamic education.